Identification of carotenoid composition in selected 'ulam' or traditional vegetables in Malaysia - Mohd Zaifuddin, Fatimah Azzahra; Mohd Hassan, Norazian; Othman, Rashidi (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Ulam or traditional vegetables in Malaysia comprise more than 120 species representing various families ranging from groundcovers, shrubs to trees. The leaves, shoots, flowers, fruits, roots and rhizomes of the vegetables are eaten fresh as salad or cooked and are consumed to add variety and flavor to the diet, as well as for their health benefits. Ulam species are rich in carbohydrate, protein, mineral and vitamin. This study established that ulam species differ greatly with respect to types and concentrations of carotenoids in leaves. A total of 10 species were evaluated for quantitative and qualitative carotenoid composition through spectrophotometry and HPLC analysis. The main carotenoids identified in these selected ulam were lutein, neoxanthin, violaxanthin, zeaxanthin and β-carotene. The ratio of these carotenoids varies between species.